2022
DOI: 10.1371/journal.pone.0262785
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and inflammatory mediators: Markers involved in interstitial damage to the pancreas in two dengue fever cases associated with acute pancreatitis

Abstract: Dengue viral (DENV) infections can lead to acute pancreatitis and associated tissue damage. This study examined the pancreas from two fatal cases of DENV for histopathological changes as well as for the detection of cytokines, and other inflammatory mediators. Tissue sections were prepared for examination by ultrastructural and histopathological techniques. Sections from the pancreas of non-infected individuals were prepared in parallel as a control. The presence of viral replication in macrophages was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…More recently, we also observed renal tissues of dengue fatal cases in children associated to DENV with the development of acute renal injury and glomerulonephritis (25). Other studies approaching dengue fatal cases evidenced alterations in histopathology and cytokines profile of other organs such as spleen, lung, heart, kidney, pancreas and placenta (23,24,(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 55%
“…More recently, we also observed renal tissues of dengue fatal cases in children associated to DENV with the development of acute renal injury and glomerulonephritis (25). Other studies approaching dengue fatal cases evidenced alterations in histopathology and cytokines profile of other organs such as spleen, lung, heart, kidney, pancreas and placenta (23,24,(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 55%
“…Caspase‐8 activation has been previously found in DENV‐infected monocytes 21 . Earlier studies have also suggested caspase‐3 activation during post‐DENV‐infection in primary human endothelial cells of umbilical vein and pancreatic tissue origin from DENV‐infected patients and C57BL/6 mice 20,22,23 . Also, caspase‐7 has been found to be activated during HSV‐1, SARS‐CoV‐2, influenza and HCV mediated infections, thereby resulting in apoptosis 24–27 .…”
Section: Discussionmentioning
confidence: 85%
“…The quantification of field image was performed by calculating the percentage of cytokine area or the number of positive cell counts using the software Image J, as previously described. 38 Each group consisted of three or four animals, and all quantification of retinal images was evaluated in a blinded manner as the mean of three or four selected images for each group.…”
Section: Methodsmentioning
confidence: 99%